Synthesis and biological activity of a profluorescent analogue of coenzyme B12. - Rosendahl, M S (1982)
We describe here the synthesis and chemical properties of linear(lin)-benzoadenosylcobalamin, a coenzyme B12 analogue that has a laterally extended nucleoside in the upper axial position. It is an effective competitive inhibitor of ribonucleotide reductase from Lactobacillus leichmannii. lin-Benzoadenosylcobalamin is nonfluorescent in solution but, on homolytic (light) or heterolytic (acid, cyanide) cleavage of the carbon-cobalt bond, forms fluorescent products. In addition, fluorescence is detectable on binding of the coenzyme analogue to ribonucleotide reductase, and the observed fluorescence polarization of the lin-benzoadenosyl moiety indicates that it is bound loosely to the enzyme when the coenzyme is partially dissociated.